2010
DOI: 10.1111/j.1420-9101.2009.01916.x
|View full text |Cite
|
Sign up to set email alerts
|

A microsatellite linkage map for Drosophila montana shows large variation in recombination rates, and a courtship song trait maps to an area of low recombination

Abstract: Current advances in genetic analysis are opening up our knowledge of the genetics of species differences, but challenges remain, particularly for out‐bred natural populations. We constructed a microsatellite‐based linkage map for two out‐bred lines of Drosophila montana derived from divergent populations by taking advantage of the Drosophila virilis genome and available cytological maps of both species. Although the placement of markers was quite consistent with cytological predictions, the map indicated large… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(29 citation statements)
references
References 58 publications
1
28
0
Order By: Relevance
“…The simulated trait effect size was based on a QTL detected for song variation in crosses between North American and Finnish D. montana (Colorado and Oulanka, that is, a different population from North America) Schafer et al, 2010;Lagisz et al, 2012). We failed to detect QTL for the same traits and genomic positions as the between-population study.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The simulated trait effect size was based on a QTL detected for song variation in crosses between North American and Finnish D. montana (Colorado and Oulanka, that is, a different population from North America) Schafer et al, 2010;Lagisz et al, 2012). We failed to detect QTL for the same traits and genomic positions as the between-population study.…”
Section: Discussionmentioning
confidence: 97%
“…We compare the within-population QTL analysis of song variation with previous work that identified QTL influencing courtship song by using between-population outbred crosses of D. montana (from Oulanka, Finland and Colorado, N. America). The detected QTL were on two chromosomes (X and 2) and one candidate gene was potentially associated with each QTL (per and fru, respectively) (Schafer et al, 2010;Lagisz et al, 2012), although it has not been confirmed whether these or other genes under the peaks are responsible for the phenotypic effects.…”
Section: Introductionmentioning
confidence: 99%
“…We worked on a cross between two strains described in Schäfer et al (2010) known to be divergent for song characters. The two genetically variable isofemale strains representing natural populations from Finland (Oulanka, O3F66) and from the USA (Colorado, C3F13) were kept under laboratory conditions for approximately 1 year before crossing.…”
Section: Insect Materials and Song Charactersmentioning
confidence: 99%
“…Earlier studies revealed significant differences in several song characters, wing shape and genital morphology, between populations from distinct geographic regions (Suvanto et al, 2000;Klappert et al, 2007;Routtu et al, 2007). The identification of polymorphic microsatellite markers in D. montana has led to the construction of a linkage map and to the mapping of QTL for song carrier frequency (FRE) differences between populations (Schäfer et al, 2010). The largest QTL mapped to an area of low recombination, containing many loci.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation